New material reveals the pelvic morphology of Caenagnathidae (Theropoda, Oviraptorosauria). (October 2020) - Rhodes, Matthew M.; Funston, Gregory F.; Currie, Philip J.
Abstract: Caenagnathids were oviraptorosaur theropods characterized by elongate hind limbs that are proposed as adaptations for either wading or enhanced cursoriality. A lack of well preserved pelvic material, however, has thus far prevented reconstruction of both the hind limb and girdle for verification of these hypotheses. Here we describe an abundance of new caenagnathid pelvic material from the Dinosaur Park Formation of Alberta, Canada. These new specimens reveal more of the anatomy of the pelvis and can be tentatively divided into three morphotypes of varying body size. Improved representation of the pelvis allows for identification of osteological correlates for caenagnathid pelvic musculature based on extant phylogenetic bracketing and direct observation of muscle attachment sites. This provides a foundation for future studies on theropod locomotion and highlights one pelvic muscle origin inconsistent with existing literature. Among the putative morphotypes, variation in correlates of pelvic muscles and proportions of pelvic bones may have had functional implications, based on patterns in extant birds. These results suggest that caenagnathids show adaptations more congruent with wading than increased cursoriality, but that morphology and function within the group varied more than previously appreciated. Highlights: New pelvic material improves understanding of caenagnathid anatomy. Delineation of three morphotypes reveals more variation than previously appreciated. Pelvic morphology and myology offer insight on locomotory style. Hypotheses of wading and cursoriality in caenagnathids are evaluated and compared.